The impact of social services development on human capital - Rajabov Utkir Dusnayevich (THE INNOVATION ECONOMY, 2026)
The article reveals the content of human capital as mental and physical abilities embodied in a person, the importance of the complex of the social sphere in the development of education, medicine, working conditions and housing, as well as the fact that time and funds invested in the social sphere are investments into human capital. It was believed that society has always been interested in educated, experienced and healthy people to work, for this it is necessary to deepen reforms in the social sphere.